Bagian Harga yang Diterima Petani (Farmer’s Share) dan Efisiensi Saluran Pemasaran Tandan Buah Segar Kelapa Sawit Petani Swadaya di Kabupaten Banyuasin - Zakaria, Zakaria; Lifianthi, Lifianthi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Zakaria Z, Lifianthi L. 2022. The share of price received by the farmer (farmer’s share) and the efficiency of the marketing channel of oil palm fresh fruit bunches of self-funding farmers in district Banyuasin Regency. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 533-543. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Marketing is an important aspect of developing self-funding smallholder oil palm plantations. The majority of the population in district Banyuasin regency are self-funding farmers of oil palm. The problems faced by oil palm self-funding farmers are the lack of transportation facilities, inadequate road access, oil palm productivity and lack of information about prices, causing self-funding smallholders to only be the recipients of prices. The objectives of this study were to (1) Describe the marketing channels for fresh fruit bunches of oil palm self-funding farmer (2) Calculate the marketing margin and the percentage share of the price received by self-funding oil palm farmer (3) Calculating the level of marketing efficiency of fresh fruit bunches (FFB) carried out by self-funding oil palm farmer. This research was conducted in District Banyuasin Regency from February to March 2022. The research method used was a survey method. The sampling method used to take samples of oil palm self-funding farmer is a simple random method with a total of 35 farmers as respondents. sampling method used to determine the sample of traders collecting snowball sampling method. The data used in this study are primary data and secondary data. The results of this study found that there was only one marketing channel pattern for oil palm fresh fruit bunches (FFB) self-funding smallholders in Sub District Air Kumbang District Banyuasin Regency which included: Self-funding farmer – Collectors – Palm oil mills. The value of the marketing margin is Rp.260.00/Kg, the value of farmer's share is 93.69% and the marketing efficiency of self-funding smallholder oil palm fresh fruit bunches is stated to be efficient with a marketing efficiency value of 5,54%.